2022
DOI: 10.1155/2022/1970591
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Dynamic Compression Mechanics of Sandstone after Coupled Alkali‐Chemical‐Dynamic Interaction

Abstract: For the purpose of analyzing the effect of the alkaline solutions on the mechanical property of sandstone impact compression, the sandstone specimens of coal mine roadway were corroded in NaOH solution with pH 7 (neutral pure water solution) and pH = 8, 9, 10, 11, and 12 for 28 d, followed by dynamic compression tests using a separated Hopkinson compression bar test device, and the microstructural changes of the specimens were measured by SEM electron microscope scanning equipment. The studies indicate that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…When the thickness of prefabricated cracks reached 3.5 mm, the internal force of the sandstone specimens was extremely uneven, the average particle size after crushing was the smallest, and the degree of crushing was the most obvious. The fitting relationship is shown in Equation (6).…”
Section: The Fractal Dimension Of the Broken Fragments After The Spec...mentioning
confidence: 99%
See 1 more Smart Citation
“…When the thickness of prefabricated cracks reached 3.5 mm, the internal force of the sandstone specimens was extremely uneven, the average particle size after crushing was the smallest, and the degree of crushing was the most obvious. The fitting relationship is shown in Equation (6).…”
Section: The Fractal Dimension Of the Broken Fragments After The Spec...mentioning
confidence: 99%
“…Li et al [2] carried out impact tests on limestone, dolomite, and sandstone. Ping et al [3][4][5][6][7] conducted impact compression tests on different types of sandstone under high-temperature and different HP conditions to study their mechanical properties and analyze their stress balance. Wang et al [8] investigated the variation in the acoustic energy of granite under combined dynamic and static loading; they found that the law of acoustic emission energy presents two distinct characteristics.…”
Section: Introductionmentioning
confidence: 99%